Chylomicron retention disease caused by a new pathogenic variant in sar1b protein: a rare case report from Syria - Leen Jamel Doya; Lava Mohammad; Razan Omran; Alexander Ali Ibrahim; Nizar Yousef; Ali Ibrahim; Mohammad Adib Houreih (BMC, 2021)
Abstract Background Chylomicron retention disease (Anderson disease) is a result for variant of the SAR1B gene. It is a rare autosomal recessive hereditary disorder with most incidence in infant. It is characterized by lipid malabsorption syndrome with fatty, chronic diarrhea, and growth retardation. Case presentation We report a case of a 19-month Syrian boy who presented with vomiting, growth failure, and chronic, fatty diarrhea. Upper gastrointestinal endoscopy showed whitish appearing duodenal mucosa and small intestinal biopsies revealed steatosis of enterocytes. Genetic testing confirmed chylomicron retention disease with the first description of variant located in the fourth helix of sar1b protein. The patient is treated with nutritional supplements and fat-soluble vitamin supplementation resulting in significant improvement. Conclusion Early endoscopy is recommended in infants with persistent vomiting and failure to thrive due to high suspicion for a disorder of hypocholesterolemia. Early diagnosis and treatment are essential to avoid serious clinical complications, especially neurological impairment.